PENGARUH PROMOSI KESEHATAN MEMAKAI METODE PENYULUHAN TERHADAP PENINGKATAN PENGETAHUAN SISWI KELAS X TENTANG KEPUTIHAN DI SMAN 5 PADANG - Rahman, Nurhamidah (Menara Ilmu, 2018)
Flour Albus is a kind of silym that comes out too much, the color is white like sago thickand slightly yellowish. If silym or mucus is not too much, not a problem. According to theWHO, the problem of reproductive health of bad women has reached 33% of the totalburden of diseases suffered by women in the world one of them is abnormal whiteness(pathological). This study aims to determine the effect of counseling on increasing theknowledge of female students at flour albus in State high school five Padang.The type of this research is quasi-experimental research (quota eksperimen desaigns),using One Group Pretest Posttest design model. The population is all students of class X inState high school five Padang. amounted to 59 people.The result of dependent paired test of T-test showed average respondent knowledge beforecounseling 8,93 ± 1,143 and after counseling 11,37 ± .0,445 with mean value difference2,441 ± 1,343, from statistic test get P. value = 0,000 (p <0,05), it can be concluded thatthere are significant differences to the level of knowledge of respondents before and aftercounseling about vaginal discharge.Suggestions for educational institutions of State high school five Padang are expected tofurther improve the provision of wider material other than whiteness but developed withother materials that can be useful for teenagers aged through UKS schools.Keywords: counseling, knowledge, Flour Albus